KONSELING KELOMPOK MENGGUNAKAN TEKNIK MODELING SIMBOLIS MELALUI FILM PENDEK UNTUK MEREDUKSI PERUNDUNGAN VERBAL - Halida, Halida; Borneo, Zaky Ibrahim Zayn (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This research aims to reduce verbal bullying by using group counseling using symbolic modeling techniques through short films for students. This type of research uses quantitative research, Quasi Experimental design, namely Pre test- Post test Control Group Design, the population is class VII students at SMPN 4 Pontianak. The sampling technique was carried out using a non-probability sampling technique. Data was collected using a verbal bullying questionnaire, distributed directly to students in class. The method used is the descriptive method, the data described are the results of the pretest and posttest from the experimental group and the control group. From this data, the average, variance, standard deviation, highest value and lowest value are calculated. The data used is interval data, the analysis is carried out using non-parametric statistics. Hypothesis testing using paired sample t-test. The research results revealed that there were significant differences in the pre-test and post-test results in the experimental class which used group counseling with symbolic modeling techniques through short films. Meanwhile, the control class used conventional group counseling. The pre-test average for the experimental class was 118.71, then after being given treatment, the level of verbal bullying decreased to 77.14. Meanwhile, the average score in the control class pre-test with conventional group counseling was 120.71, decreasing to 105.14. Based on the output of Pair 1, a sig value is obtained. (2-tailed) of 0.000 < 0.05 means there is a difference in the average level of verbal bullying among victims for the pre-test and post-test of the experimental class. Group counseling using symbolic modeling techniques using short films and discussions can reduce verbal bullying among students. Group counseling with short films shown is able to influence students' souls and feelings so that they are able to be stronger and tougher in facing verbal bullying from around students.